Cervical myelopathy due to complex Atlanto‐axial malformation including partial atlantal dorsal arch aplasia in a domestic rabbit. (29th January 2018) - Nessler, J. N.; Attig, F.; Thöle, M.; Raddatz, B.; Beineke, A.; Fehr, M.; Tipold, A.; Stein, V. M.
Abstract : A 1‐year‐old dwarf rabbit was presented with sub‐acute progressive tetraparesis. Radiography, CT and MRI revealed compressive cervical myelopathy secondary to a complex atlanto‐axial malformation including partial aplasia of the atlantal dorsal arch, dens malformation, malarticulation and lateral atlanto‐occipital displacement. Owners decided against surgical treatment and elected conservative treatment including analgesia with non‐steroidal anti‐inflammatory drugs, cage rest and physiotherapy. Within 2 months clinical signs deteriorated and the owner elected euthanasia. Subsequent necropsy confirmed imaging findings. Similar cases described in humans and dogs suggest that partial aplasia of the dorsal arch of the atlas might often be an asymptomatic radiologic finding in these species. In contrast, this first description of a similarly affected rabbit demonstrates that complex atlanto‐axial malformations can cause severe clinical signs.